Socializing in the suburbs: relationships between neighbourhood design and social interaction in low-density housing contexts. Issue 1 (2nd January 2020) - Abass, Zainab Ibrahim; Andrews, Fiona; Tucker, Richard
ABSTRACT: This study investigates interrelationships between correlates of social interaction, levels of social activity and common neighbourhood design characteristics of low-density suburbs. Qualitative and quantitative methods were combined. Analysis of 247 surveys of residents in three low-density Australian suburbs confirmed interrelationships between levels of social activity, social interaction correlates and five groups of physical characteristics: (1) street layout, (2) pedestrian environment, (3) neighbourhood connectivity, (4) public space provision and (5) dwelling form. After allowing for the effect of socio-demographic and social proclivity selection factors, street type, tree coverage and provision of open space were found to significantly predict Neighbourhood Contentment.